An analysis of stroke parameters during 50-m and 100-m freestyle events for male elite swimmers in Japan National Swimming Championship - Okuno, K.; Ikuta, Y.; Wakayoshi, K.; Nomura, T.; Miyashita, M. (2001)
The purpose of this study was to investigate the stroking phase variables in 50-m and 100-m freestyle events to improve swimming coaching. Eighteen male Japanese elite competitors who participated in both 50-m and 100-m free style events in the 1999 Japan National Swimming Championship were subjects in this study. The subjects were recorded by video-camera and analyzed to determine stroking phase velocity (SV), stroke length (SL), stroke frequency (SF) and stroke index (SI) at each stroking phase (50-m event: 10-45m, 100-m event: 10-45m and 57.5-95m). These variables were also analysed to assess the correlation shown among the three stroking phases. The number of subjects made up 52.9% of all swimmers in the 50-m event of this meet. The value of SV50 was higher than SV1 and SV2, and SV1 was greater than SV2. The value of SF50 was greater than SF1 and SF2, and SF1 was greater than SF2. The value of SL50 was smaller than SL1 and SL2, and SL1 was greater than SL2. It was a characteristic that SV depended on SF in the 50-m event, unlike in the 100-m event where no dependency was apparent. The performance of swimmers in the 100-m event required a higher rate of swimming economy with greater swimming efficiency on 1st half of the stroking phase. It was considered important to find the optimal combination of SL and SF values for each swimmer with energy supply adapted for each race distance. It was also considered that selection of either the 50-m or 100-m event based on physical characteristic of the elite swimmers would be effective in developing swimmer performance, race strategies, and coaching techniques.